Process Design and Evaluation of a Digital Shadow - Bekric, Emir; Sandström, John (My University, 2022)
Digital shadows and Digital Twins are fundamental to the concept of Industry 4.0. They allow for in-depth analysis of operations, which in turn leads to more stream lined businesses. In this project, a Digital Shadow will be designed and accompanied by two different types of visualizations. The Digital Shadow will be based on a man ufacturing company, Bror Tonsjö AB, located north of Gothenburg, Sweden. In summary, the project consisted of creating visualizations and implementing real time data. The visualizations were either designed by using 3D-models or point cloud technology. When the visualization was completed, a server was hosted through Python and OPC UA for the purpose of creating the variables to be used in the Digital Shadow. The visualizations were connected to a server that hosted the variables and controlled the behavior of the layout. Finally, feedback was gathered through qualitative interviews to evaluate the process design and how the Digital Shadow could be improved in relation to the predetermined research questions. The result of this project shows that Digital Shadows hold many use cases and could streamline many types of industries. A Digital Shadow is very versatile and could be designed to suit everything from manufacturing industries to grocery stores. The versatility extends into internal business sectors as well, since a Digital Shadow could be equally useful for a manager or a logistics worker, depending on the design and accessibility. Due to the different methods of integrating this technology, it is possible to tailor the complexity of the Digital Shadow to suit unique situations and find value.
Keywords: Digital Shadow, Digital Twin, OPC UA, Industry 4.0, IoT, Visualization, Points of interest, Connectivity, Digitalization, Real-time data, Point clouds.